PC Remote Control Software and Remote Access Software - Johari, Mohd Helmi; Ayob, Mohd Fairullazi (2017)
The ICT unit of KAED has prepared and table a paper of PC Remote Control Software and Remote Access Software that can help ICT Technician to increase efficiency and productivity on essential network operations: •Update software •Troubleshoot PCs and servers •Switch computers on and off remotely